Treatment of patellofemoral chondropathy with BIOART - Ferdinando Franzoni; Jonathan Fusi; Marco Ceccarelli; Andrea Petrocchi; Matteo Vitale; Marco Letari; Riccardo Banducci; Veronica Santini; Giorgia Scarfò; Eugenio Cerri; Fabio Galetta (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2020)
The patellofemoral syndrome is characterized by morpho-functional alterations, mainly caused by a misalignment or dysplasia of the patella and/or femoral trochlea. The treatment of this chondropathy is mostly conservative. Furthermore, clinical practice seeks to use "chondroprotective" drugs and supplements, capable of counteracting degenerative processes, favoring the normalization of articular cartilage and synovial fluid. However, to date there are no effective and lasting treatments aimed at restoring joint function. Objective: The aim of the study is to evaluate the efficacy and tolerability of the medical device "Bioart", based on equine collagen, in patients suffering from patellofemoral chondropathy.  Results: All patients enrolled in the study (N = 23) showed a consistent improvement in the algic component and functional limitation related to the chondro-arthrosic process within 12 weeks.  Conclusion: The data showed that Bioart is able to improve the clinical-functional picture of treated patients. Furthermore, the absence of side effects and cost reduction improved adherence to therapy.